A proteolytic artifact associated with the lysis of bacteria by egg white lysozyme. - Oliver, C N (1983)
Polyacrylamide gel electrophoresis of cell-free extracts of Escherichia coli that had been grown in a medium containing 32Pi disclosed the presence of several 32P-labeled proteins. Comparison of the electrophoretic patterns obtained in the presence of carrier unlabeled purified E. coli glutamine synthetase before and after treatment with trypsin, subtilisin, or snake venom phosphodiesterase showed that most of the 32P was present in the adenylyl moieties of adenylylated glutamine synthetase. Low molecular weight 32P-labeled degradation products of glutamine synthetase were also observed in extracts prepared by treatment of cells with lysozyme but not in extracts prepared by sonic oscillation. The degradation of glutamine synthetase in lysozyme-prepared extracts is likely due to an intrinsic proteolytic activity of egg white lysozyme. Proteolysis probably occurs at the esterase site of lysozyme described by Piszkiewicz and Bruice [Piszkiewicz, D. & Bruice, T.C. (1968) Biochemistry 7, 3037-3047]. Selective carboxymethylation of lysozyme histidine-15 leads to simultaneous loss of esterase and protease activities but only to partial loss of lytic activity. In view of these findings, caution is needed in the interpretation of results obtained with extracts of cells prepared by lysozyme treatment, especially when such extracts are used to investigate the properties of proteolytic enzymes.